Preparation method of polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel

The preparation of polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogels through simple freezing and dissolution preparation methods has solved the problems of high cost and complex process in the existing technology to prepare bone replacement materials, and achieved good biocompatibility bone replacement material is suitable for mass production and improves the osteogenic effect of bone defects.

CN119113205APending Publication Date: 2024-12-13XIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411290381.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art requires complex reaction reagents and liquid nitrogen when preparing bone replacement materials, which is costly and difficult to control process parameters, limiting the effectiveness of bone repair.

Method used

Using a simple freezing and dissolution preparation method, polyvinyl alcohol-magnesium-doped hydroxyapatite suspension and chitosan solution were prepared by configuring polyvinyl alcohol solution, magnesium-doped hydroxyapatite suspension and chitosan solution, combined with ultrasonic dispersion and thermal stirring, polyvinyl alcohol-doped hydroxyapatite- Chitosan hydrogel achieves pore size and degradability of osteocyte growth.

Benefits of technology

It has achieved a bone substitute material with good biocompatible, low cost and easy-to-use technology. It has soft and shaped properties, is suitable for large-scale production, and improves the bone formation effect of bone defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119113205A_ABST
    Figure CN119113205A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel, in particular to a method for preparing a moldable bone grafting hydrogel material capable of guiding bone growth by utilizing the characteristic that a polyvinyl alcohol solution becomes gel at room temperature and combining a magnesium-doped hydroxyapatite suspension and a chitosan solution. The method comprises the following steps: adopting a polyvinyl alcohol solution as a matrix, adding deionized water into magnesium-doped hydroxyapatite powder, carrying out ultrasonic treatment to prepare a suspension, adding a chitosan solution to promote dispersion of magnesium-doped hydroxyapatite, uniformly mixing the three liquids under high-temperature stirring, putting into a mold for defoaming and shaping, freezing in a refrigerator, taking out the mold for unfreezing, and after complete unfreezing, carrying out vacuum drying to obtain the magnesium-doped hydroxyapatite composite material. Repeatedly freezing and unfreezing to form hydrogel; two polymer materials of polyvinyl alcohol and chitosan are mixed with magnesium-doped hydroxyapatite to prepare the hydrogel, the cost is low, the hydrogel is simple and easy to repeat, and the formed hydrogel is soft, elastic and good in biocompatibility and can be used for filling bone defects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogel materials, and particularly relates to a method for preparing a polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel. Background Art

[0002] Hydrogel material is a kind of degradable polymer material, which has a wide range of applications in biomedicine due to its unique swelling property and biocompatibility. After modification, hydrogel has better performance and can provide temporary mechanical support for bone injury areas. Among them, polyvinyl alcohol has the advantages of low cytotoxicity, good mechanical properties, and good biocompatibility. Its solution has good fluidity at high temperature and can form gel when cooled at room temperature. It has a good effect in the field of cartilage repair after compounding with hydroxyapatite. The porous scaffold formed by compounding hydroxyapatite and chitosan and cold drying is a good bone repair material.

[0003] Chinese patent CN201010224750.9 discloses a method for preparing a porous hydroxyapatite / chitosan / polyvinyl alcohol composite material with large pores, belonging to the field of biomedical bone materials. A porous hydroxyapatite / chitosan / polyvinyl alcohol bone substitute material three-phase composite material with large pores (about 200 μm) and interconnected is prepared from calcium nitrate tetrahydrate, diammonium hydrogen phosphate, chitosan and polyvinyl alcohol. Small ice particles are made by using the freezing effect of liquid nitrogen, and the ice particles are pressed into the slurry. The preparation process is relatively complicated and the cost of using liquid nitrogen is relatively high. Summary of the invention

[0004] The present invention proposes a simple freezing and dissolving method to prepare magnesium-doped hydroxyapatite / chitosan / polyvinyl alcohol bone substitute material, which can realize internal pores and good degradability, which is conducive to the growth of bone cells. It does not require complicated reaction reagents and liquid nitrogen ice particle making process, which is not only low in cost, but also easy to control process parameters, which is conducive to bone repair.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel comprises the following steps:

[0007] Step 1, prepare polyvinyl alcohol solution:

[0008] Weigh polyvinyl alcohol powder into a beaker and add deionized water, and heat and stir in a heating mixer until the polyvinyl alcohol is completely dissolved to obtain a polyvinyl alcohol solution;

[0009] Step 2, preparing a magnesium-doped hydroxyapatite suspension solution:

[0010] The magnesium-doped hydroxyapatite is prepared by replacing a part of the calcium source with the magnesium source during the synthesis of the hydroxyapatite, and the magnesium-doped hydroxyapatite and deionized water are mixed and stirred thoroughly and ultrasonically dispersed in an ultrasonic instrument to prepare a magnesium-doped hydroxyapatite suspension;

[0011] Step 3, prepare chitosan solution:

[0012] Weigh chitosan powder and add it to 1% acetic acid solution, stir on a magnetic stirrer until the chitosan powder is completely dissolved to obtain a chitosan solution;

[0013] Step 4, slowly adding the magnesium-doped hydroxyapatite suspension into the polyvinyl alcohol solution heated and stirred on a heated stirrer and stirring together to obtain a uniformly mixed milky white solution;

[0014] Step 5, slowly adding the chitosan solution into the milky white solution, and fully stirring on a heated stirrer to obtain a polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution;

[0015] Step 6, placing the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution into a mold, shaking it sufficiently, and then removing huge bubbles in the solution in a water bath, so that the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution fully fills the mold;

[0016] Step 7, putting the mold filled with the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution into a refrigerator for freezing, then taking it out and thawing it at room temperature, and continuing to put the mold into the refrigerator, repeating freezing and thawing, to obtain the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel.

[0017] Furthermore, in step 1, 1.5-4.5 g of polyvinyl alcohol powder and 8.5-25.5 g of deionized water are weighed, the heating temperature in the heating stirrer is 90° C., and the stirring process is carried out using a magnetic stirrer for 1-2 h.

[0018] Furthermore, in step 2, 0.25-0.75 g of magnesium-doped hydroxyapatite powder and 4.75-14.25 g of deionized water are mixed.

[0019] Furthermore, in step 2, stirring is performed for 5 minutes before ultrasonication to obtain a suspension without large particles or powder remaining, and then ultrasonic dispersion is performed for 1 hour.

[0020] Furthermore, in step 3, 0.2-0.6 g of chitosan powder and 9.8-29.4 g of 1% acetic acid solution were weighed and stirred with a magnetic stirrer for 1-2 h.

[0021] Furthermore, in step 4, the magnesium-doped hydroxyapatite suspension is slowly added into the polyvinyl alcohol solution heated and stirred at 90° C. on a heated stirrer and stirred together for 30 minutes.

[0022] Furthermore, in step 5, the chitosan solution is slowly added into the milky white solution and stirred on a heated stirrer at 90° C. for 30 min.

[0023] Furthermore, the specific method of step 6 is: after slowly injecting the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution into the mold, the mold is lifted up by 10 cm and freely dropped onto the table, which is repeated 10 times, and then placed in a constant temperature water bath at 60° C. for 30 minutes.

[0024] Furthermore, the specific method of step 7 is: put the mold filled with the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution into a refrigerator at -25°C for 8 hours, then take it out and thaw it at room temperature for 1-2 hours, continue to put the mold into the refrigerator, repeat freezing, and thaw 4 times to obtain the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The present invention provides a method for preparing a polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel, which utilizes the property of polyvinyl alcohol solution to gel at room temperature, and combines a magnesium-doped hydroxyapatite suspension and a chitosan solution to prepare a method for preparing a plastic bone graft hydrogel material that can be used to guide bone growth.

[0027] 2. The hydrogel material is soft and elastic and has good plasticity. It can be preformed to fill bone defects, maximize the combination of shape and bone defects, and improve the osteogenesis effect.

[0028] 3. The material has good biocompatibility, low cost, simplicity and good repeatability, and is suitable for large-scale production. It is a more convenient and safe bone replacement filling material. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The present invention is a process flow chart of a method for preparing a polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel;

[0030] Figure 2 The SEM images of the morphology of the PVA / Mg-HA hydrogel sample of Example 1 of the present invention, Figures A and B are surface morphology images at magnifications of 5000, 10000, 20000, and 50000 times, respectively;

[0031] Figure 3 The SEM images of the morphology of the PVA / Mg-HA / CS hydrogel sample in Example 1 of the present invention, Figures ad are surface morphology images at magnifications of 1000, 5000, 10000, and 2000 times, respectively;

[0032] Figure 4 This is an EDS layered image of the PVA / Mg-HA / CS hydrogel surface scanned by an energy dispersive spectrometer equipped with a scanning electron microscope in Example 1 of the present invention;

[0033] Figure 5 This is an observation diagram of the live and dead cell test results of the PVA / Mg-HA / CS hydrogel sample of Example 1 of the present invention using the staining method. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0035] like Figure 1 As shown, a method for preparing polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel, the specific steps are as follows:

[0036] Step 1, prepare polyvinyl alcohol solution:

[0037] Weigh 1.5-4.5 g of polyvinyl alcohol powder into a beaker and add 8.5-25.5 g of deionized water, heat and stir at 90° C. in a heating stirrer for 1-2 h until the polyvinyl alcohol is completely dissolved to obtain a polyvinyl alcohol solution;

[0038] Step 2, preparing a magnesium-doped hydroxyapatite suspension solution:

[0039] The magnesium-doped hydroxyapatite is prepared by replacing a portion of the calcium source with a magnesium source during the synthesis of hydroxyapatite, mixing 0.25-0.75 g of magnesium-doped hydroxyapatite powder and 4.75-14.25 g of deionized water and stirring them for 5 minutes to obtain a suspension without large particles or powder remaining, and then ultrasonically dispersing in an ultrasonic instrument for 1 hour to prepare a magnesium-doped hydroxyapatite suspension;

[0040] Step 3, prepare chitosan solution:

[0041] Weigh 0.2-0.6g chitosan powder and add 9.8-29.4g 1% acetic acid solution, and stir on a magnetic stirrer for 1-2h to completely dissolve the chitosan powder;

[0042] Step 4, slowly add the magnesium-doped hydroxyapatite suspension into the polyvinyl alcohol solution stirred at 90° C. on a heated stirrer and stir together for 30 minutes to obtain a uniformly mixed milky white solution.

[0043] Step 5, slowly adding the chitosan solution into the milky white solution, and fully stirring at 90° C. for 30 min on a heated stirrer to obtain a polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution;

[0044] Step 6, after slowly injecting the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution into the mold, the mold is lifted up by 10 cm and freely dropped onto the table, and the process is repeated 10 times. After sufficient shaking, the huge bubbles in the solution are removed by placing the mold in a 60° C. constant temperature water bath for 30 min, so that the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan solution fully fills the mold;

[0045] Step 7, place the mold filled with the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution into a refrigerator at -25°C for 8 hours, then take it out and thaw it at room temperature for 1-2 hours, continue to put the mold into the refrigerator, repeat freezing and thawing 4 times, and you can get the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel.

[0046] Example 1

[0047] Step 1, prepare a 15% polyvinyl alcohol solution: weigh 1.5 g of polyvinyl alcohol powder into a beaker and add deionized water to 10 g, heat and stir at 90° C. in a heating mixer for 1 h until the polyvinyl alcohol powder is completely dissolved to obtain a 15% polyvinyl alcohol solution;

[0048] Step 2, preparing a magnesium-doped hydroxyapatite suspension solution: preparing magnesium-doped hydroxyapatite by replacing a portion of the calcium source with a magnesium source during the synthesis of hydroxyapatite, mixing 0.25 g of magnesium-doped hydroxyapatite powder and 4.75 g of deionized water, and stirring them for 5 minutes to obtain a suspension without large particles or powder remaining, and ultrasonically dispersing in an ultrasonic instrument for 1 hour to prepare a magnesium-doped hydroxyapatite suspension;

[0049] Step 3, prepare 2% chitosan solution: weigh 0.2g chitosan powder, add 9.8g 1% acetic acid solution and stir on a magnetic stirrer for 1h until the chitosan powder is completely dissolved;

[0050] Step 4, slowly adding the magnesium-doped hydroxyapatite suspension into the 15% polyvinyl alcohol solution heated and stirred at 90° C. on a heated stirrer and stirring together for 30 minutes to obtain a uniformly mixed milky white solution;

[0051] Step 5, slowly adding 2% chitosan solution into the milky white solution, and stirring thoroughly at 90° C. for 30 min on a heated stirrer to obtain a polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution;

[0052] Step 6, after slowly injecting the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution into the mold, the mold is lifted up by 10 cm and freely dropped onto the table, and the process is repeated 10 times. After sufficient shaking, the huge bubbles in the solution are removed by placing the mold in a 60° C. constant temperature water bath for 30 min, so that the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan solution fully fills the mold;

[0053] Step 7, place the mold filled with the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution into a refrigerator at -25°C for 8 hours, then take it out and thaw it at room temperature for 1 hour, continue to put the mold into the refrigerator, repeat the freezing, and after thawing 4 times, the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel can be obtained.

[0054] Example 2

[0055] Step 1, prepare 15% polyvinyl alcohol solution: weigh 3g polyvinyl alcohol powder into a beaker and add 27g deionized water, heat and stir at 90°C in a heating stirrer for 2h until the polyvinyl alcohol powder is completely dissolved to obtain a 15% polyvinyl alcohol solution;

[0056] Step 2, preparing a magnesium-doped hydroxyapatite suspension solution: preparing 5% magnesium-doped hydroxyapatite by replacing a portion of the calcium source with a magnesium source during the synthesis of hydroxyapatite, mixing 0.5 g of magnesium-doped hydroxyapatite powder and 9.5 g of deionized water and stirring for 5 minutes to obtain a suspension without large particles or powder remaining, and ultrasonically dispersing in an ultrasonicator for 1 hour to prepare a magnesium-doped hydroxyapatite suspension;

[0057] Step 3, prepare 2% chitosan solution: weigh 0.4g chitosan and add 19.6g 1% acetic acid solution and stir on a magnetic stirrer for 2h until the chitosan powder is completely dissolved;

[0058] Step 4, slowly add the magnesium-doped hydroxyapatite suspension into the 15% polyvinyl alcohol solution heated and stirred at 90° C. on a heated stirrer and stir together for 30 minutes to obtain a uniformly mixed milky white solution.

[0059] Step 5, slowly adding 2% chitosan solution into the milky white solution, heating and stirring at 90° C. for 30 min on a heating stirrer to obtain a polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution;

[0060] Step 6. After slowly injecting the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution into the mold, the mold is lifted up by 10 cm and freely dropped onto the table, and the process is repeated 10 times. After sufficient shaking, the huge bubbles in the solution are removed by placing the mold in a 60°C constant temperature water bath for 30 minutes, so that the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan solution fully fills the mold.

[0061] Step 7, place the mold filled with the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution into a refrigerator at -25°C for 8 hours, then take it out and thaw it at room temperature for 2 hours, continue to put the mold into the refrigerator, repeat the freezing, and after thawing 4 times, you can get the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel.

[0062] Example 3

[0063] Step 1, prepare a 15% polyvinyl alcohol solution: weigh 4.5 g of polyvinyl alcohol powder into a beaker and add 25.5 g of deionized water, stir at high temperature for 2 h in a heating stirrer until the polyvinyl alcohol is completely dissolved to prepare a polyvinyl alcohol solution with a mass fraction of 15%.

[0064] Step 2, prepare a magnesium-doped hydroxyapatite suspension solution, prepare 5% magnesium-doped hydroxyapatite by replacing a portion of the calcium source with a magnesium source during the synthesis of hydroxyapatite, add 0.75g of magnesium-doped hydroxyapatite powder to 14.25g of deionized water and stir well for 5 minutes to obtain a suspension without large particles or powder remaining, and ultrasonically disperse in an ultrasonic instrument for 1 hour to prepare a magnesium-doped hydroxyapatite suspension.

[0065] Step 3, prepare 2% chitosan solution: weigh 0.6 g chitosan powder and add 29.4 g 1% acetic acid solution, and stir on a magnetic stirrer for 2 h until the chitosan powder is completely dissolved.

[0066] Step 4, slowly add the magnesium-doped hydroxyapatite suspension into the 15% polyvinyl alcohol solution heated and stirred at 90° C. on a heated stirrer and stir together for 30 minutes to obtain a uniformly mixed milky white solution.

[0067] Step 5, slowly adding the 2% chitosan solution into the milky white solution, fully heating and stirring at 90° C. on a heating stirrer for 30 minutes to obtain a polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution.

[0068] Step 6, after slowly injecting the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution into the mold, the mold is lifted up by 10 cm and freely dropped onto the table, and the process is repeated 10 times. After sufficient shaking, the huge bubbles in the solution are removed by placing the mold in a 60° C. constant temperature water bath for 30 min, so that the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan solution fully fills the mold;

[0069] Step 7, place the mold filled with the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution into a refrigerator at -25°C for 8 hours, then take it out and thaw it at room temperature for 2 hours, continue to put the mold into the refrigerator, repeat freezing and thawing 4 times to obtain the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel.

[0070] The PVA / Mg-HA / CS hydrogel and PVA / Mg-HA hydrogel samples prepared in Example 1 of the present invention were freeze-dried and subjected to surface morphology analysis using a scanning electron microscope. The morphology diagrams are as follows: Figure 2 and Figure 3 shown. Figure 2 The substrate of (a) was found to have traces of being cracked by an electron beam, which was determined to be organic phase PVA. Figure 2 (b) It was found that the Mg-HA group was embedded in the PVA matrix. Figure 2(c) It can be clearly seen that Mg-HA is clustered together. Figure 2 (d) It can be seen that Mg-HA is short rod-shaped and nanoscale. Combined with the SEM image analysis of PVA / Mg-HA / CS hydrogel, Figure 3 The uneven surface in (a) indicates that Mg-HA is not only embedded in the surface but also that Mg-HA groups are encapsulated in the PVA matrix. Figure 3 (b) shows that the aggregated objects now appear completely different from Figure 2 The appearance of Figure 3 (c) It can be seen that the agglomerates have thin flakes, and short rod-like substances are distributed between the flakes. Figure 3 (d) It can be seen more clearly that CS is in the form of sheets on the PVA matrix and short rod-shaped Mg-HA is distributed between the CS sheets. This structure proves the sufficient combination between the PVA / Mg-HA / CS components.

[0071] Using EDS detection, the sample of Example 1 was scanned to detect its surface element distribution, such as Figure 4 As shown in the figure, it can be seen that the Mg, Ca, P elements representing Mg-HA, the C, O elements representing PVA and the N element representing CS are evenly distributed in the cold-dried PVA / Mg-HA / CS hydrogel sample, proving that the composition of the material is correct.

[0072] The cytotoxicity and biocompatibility of the sample in Example 1 were determined by using human gingival fibroblasts to perform a live-dead cell test. Figure 5 As shown, in living cells, esterase Calcein-AM is cut by esterase in the cell to form membrane-impermeable polar molecule Calcein, which is retained in the cell and emits strong green fluorescence. Therefore, the green-stained area is the observed living cell. PI cannot pass through the cell membrane of living cells, but can only pass through the disordered area of ​​the dead cell membrane to reach the cell nucleus and embed into the cell's DNA double helix to produce red fluorescence. Therefore, the red area is the dead cell. It can be observed that the cell death rate is low and the survival rate is high, which can prove that PVA / Mg-HA / CS hydrogel has low cytotoxicity to human gingival fibroblasts after specific treatment under experimental conditions and has good biocompatibility.

[0073] The above-mentioned embodiments only express the specific implementation of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. A method for preparing polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel, characterized in that: The following steps are involved: Step 1, prepare polyvinyl alcohol solution: Weigh polyvinyl alcohol powder into a beaker and add deionized water, and heat and stir in a heating mixer until the polyvinyl alcohol is completely dissolved to obtain a polyvinyl alcohol solution; Step 2, preparing a magnesium-doped hydroxyapatite suspension solution: The magnesium-doped hydroxyapatite is prepared by replacing a part of the calcium source with the magnesium source during the synthesis of the hydroxyapatite, and the magnesium-doped hydroxyapatite and deionized water are mixed and stirred thoroughly and ultrasonically dispersed in an ultrasonic instrument to prepare a magnesium-doped hydroxyapatite suspension; Step 3, prepare chitosan solution: Weigh chitosan powder and add it to 1% acetic acid solution, stir on a magnetic stirrer until the chitosan powder is completely dissolved to obtain a chitosan solution; Step 4, slowly adding the magnesium-doped hydroxyapatite suspension into the polyvinyl alcohol solution heated and stirred on a heated stirrer and stirring together to obtain a uniformly mixed milky white solution; Step 5, slowly adding the chitosan solution into the milky white solution, and fully stirring on a heated stirrer to obtain a polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution; Step 6, placing the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution into a mold, shaking it sufficiently, and then removing huge bubbles in the solution in a water bath, so that the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution fully fills the mold; Step 7, putting the mold filled with the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution into a refrigerator for freezing, then taking it out and thawing it at room temperature, and continuing to put the mold into the refrigerator, repeating freezing and thawing, to obtain the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel.

2. The method for preparing a polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel according to claim 1, characterized in that: In step 1, 1.5-4.5 g of polyvinyl alcohol powder and 8.5-25.5 g of deionized water are weighed, the heating temperature in the heating stirrer is 90° C., and the stirring process is carried out using a magnetic stirrer for 1-2 h.

3. The method for preparing a polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel according to claim 1, characterized in that: In step 2, 0.25-0.75 g of magnesium-doped hydroxyapatite powder and 4.75-14.25 g of deionized water are mixed.

4. The method for preparing a polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel according to claim 1, characterized in that: In step 2, stirring is performed for 5 minutes before ultrasonication to obtain a suspension without large particles or powder remaining, and then ultrasonic dispersion is performed for 1 hour.

5. The method for preparing a polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel according to claim 1, characterized in that: In step 3, 0.2-0.6 g of chitosan powder and 9.8-29.4 g of 1% acetic acid solution were weighed and stirred with a magnetic stirrer for 1-2 h.

6. The method for preparing a polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel according to claim 1, characterized in that: In step 4, the magnesium-doped hydroxyapatite suspension is slowly added to the polyvinyl alcohol solution heated and stirred at 90° C. on a heated stirrer and stirred together for 30 minutes.

7. The method for preparing a polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel according to claim 1, characterized in that: In step 5, the chitosan solution is slowly added into the milky white solution and stirred thoroughly on a heated stirrer at 90° C. for 30 min.

8. The method for preparing polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel according to claim 1, characterized in that: The specific method of step 6 is: after slowly injecting the polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution into the mold, the mold is lifted up by 10 cm and freely dropped to the table, which is repeated 10 times, and then placed in a constant temperature water bath at 60° C. for 30 minutes.

9. The method for preparing polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel according to claim 1, characterized in that: The specific method of step 7 is: put the mold filled with polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan mixed solution into a refrigerator at -25°C for 8 hours, then take it out and thaw it at room temperature for 1-2 hours, continue to put the mold into the refrigerator, repeat freezing, and thaw 4 times to obtain polyvinyl alcohol-magnesium-doped hydroxyapatite-chitosan hydrogel.